Does performance-based remuneration improve outcomes in the treatment of hip fracture?: results from the WHiTE multicentre hip fracture cohort. (1st May 2021) - Griffin, Xavier L.; Achten, Juul; Parsons, Nick; Costa, Matt L.
Abstract : Aims: The aim of this study was to determine whether national standards of best practice are associated with improved health-related quality of life (HRQoL) outcomes in hip fracture patients. Methods: This was a multicentre cohort study conducted in 20 acute UK NHS hospitals treating hip fracture patients. Patients aged ≥ 60 years treated operatively for a hip fracture were eligible for inclusion. Regression models were fitted to each of the "Best Practice Tariff" indicators and overall attainment. The impact of attainment on HRQoL was assessed by quantifying improvement in EuroQol five-dimension five-level questionnaire (EQ-5D-5L) from estimated regression model coefficients. Results: A total of 6, 532 patients provided both baseline and four-month EQ-5D-5L, of whom 1, 060 participants had died at follow-up. Best practice was achieved in the care of 57% of participants; there was no difference in age, cognitive ability, and mobility at baseline for the overall attainment and non-attainment groups. Attaining at least 'joint care by surgeon and orthogeriatrician', 'delirium assessment', and 'falls assessment' was associated with a large, clinically relevant increase in four months EQ-5D-5L of 0.094 (bootstrapped 95% confidence interval (CI) 0.046 to 0.146). Conclusion: National standards with enhanced remuneration in hip fracture care results in improvement in individual patients' HRQoL. Cite this article: Bone Joint J  2021;103-B(5):881–887.